Nonsteady-state mathematical modelling of H2SO4-catalysed alkylation of isobutane with alkenes - Ivashkina E. N. Elena Nikolaevna; Ivanchina E. D. Emilia Dmitrievna; Dolganov I. M. Igor Mikhailovich; Chuzlov V. A. Vyacheslav Alekseevich; Kotelnikov A. A. Aleksandr Aleksandrovich; Dolganova I. O. Irena Olegovna; Khakimov R. A. Rustam Anvarovich (2021, 2021)
Title screen